Surface and honeycomb core damage in adhesively bonded aluminum sandwich panels subjected to low-velocity impact. (1st February 2022) - Sun, Mengqian; Wowk, Diane; Mechefske, Chris; Alexander, Evan; Kim, Il Yong
Abstract: The effect of the adhesive geometry on the impact damage of adhesively bonded aluminum sandwich panels was studied experimentally and numerically. Both the physical testing and the finite element results show that the core damage depth is dependent on the adhesive fillet height and can be linearly correlated with the dent depth. The focus of the finite element simulation is on representing the adhesive fillet height and the constraint that it provides for the cell walls at the interface with the face-sheet. A hybrid method combining the numerical study and the Bayesian method was proposed to predict the range of core damage depths from the numerical simulations based on the variability of the adhesive fillets. The variation of the adhesive fillet height between different cell walls significantly influences the core damage depth and cannot be ignored when predicting the range of the core damage depth. The non-uniform distribution of the adhesive fillets causes the core damage depth to vary within a range of up to 20% of the core thickness for the panel configurations considered in this study.